Determinant of foreign direct investment in Malaysia / Ahmad Safuan Sufian - Sufian, Ahmad Safuan (Faculty of Business and Management, 2018)
This study examines the relationships that between foreign direct investment (FDI) and the determinants economic growth (GDP), exchange rate (EXC), inflation rate (INF) and trade openness (TRD) from the year of 1985 to 2015 which contains yearly data. The data for this study has been tested by using Ordinary Least Square methods in order to define the statistical relationship among the variables. The result of this study show that there is a significant relationship between the foreign direct investment inflows and the economic growth, exchange rate and inflation rate, while Trade openness (TRD) did not have any relationship with the FDI. Lastly, the most influential factor that provide huge impact for foreign direct investment inflows in Malaysia is inflation rate.